Structure and Circulation of Atlantic Water Masses in the St. Anna Trough in the Kara Sea - Osadchiev, Alexander; Viting, Kirill; Frey, Dmitry; Demeshko, Darya; Dzhamalova, Alina; Nurlibaeva, Alina; Gordey, Alexandra; Krechik, Victor; Spivak, Eduard; Semiletov, Igor; Stepanova, Natalia (Frontiers in Marine Science, 2022)
The inflow of warm and saline Atlantic water from the North Atlantic to the Western Arctic is provided by two branches, namely, the Fram Strait branch water and the Barents Sea branch water. The pathways of these branches merge at the St. Anna Trough, and then both branches propagate eastward along the continental slope, albeit at different depths. As a result, the local interaction between these branches in the trough affects the properties of the large-scale Atlantic water flow to the Eastern Arctic and the deep Arctic basins. In this study, we report extensively in situ measurements with high spatial coverage (56 hydrological stations organized into 7 transects) in the St. Anna Trough, obtained in August and October 2021. Based on these data, we reconstructed the thermohaline structure and circulation in this area and obtained new insights, which are crucial for the assessment of the interaction and heat balance of water masses in the trough. First, we state that the majority of the Fram Strait branch water is recirculated in the trough within the stable cyclonic gyre, while a smaller fraction returns to the continental slope. The formation of this gyre increases the residence time of the Fram Strait branch water in the trough and decreases the intensity of water and heat exchange between the trough and the continental slope. Second, we describe the dynamic interaction between the northward flow of the Barents Sea branch water and the surface layer. It causes intense transport of warm surface water from the Kara and Barents seas adjacent to the Novaya Zemlya toward the continental slope and its mixing with the Barents Sea branch water along the eastern part of the trough. These processes result in increased surface temperature at the eastern part of the trough, which enhances ice melting at the study area and increases the duration of the ice-free period.